Draft Genome Sequences of Three Virulent Streptococcus thermophilus Bacteriophages Isolated from the Dairy Environment in the Veneto Region of Italy - da Silva Duarte, Vinícius (Genome Announc, 2018)
Streptococcus thermophilus, a very important dairy species, is constantly threatened by phage infection. We report the genome sequences of three S. thermophilus bacteriophages isolated from a dairy environment in the Veneto region of Italy. These sequences will be used for the development of new strategies to detect and control phages in dairy environments.